Etika Jurnalistik, Pada Pemberitaan Prostitusi Online Vanessa Angel di Jatim.Tribunnews.Com - Ahmad Khairul Nuzuli Ahmad Khairul Nuzuli; Wahyu Krisitian Natalia Wahyu Krisitian Natalia (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
The purpose of this study is to see how the implementation of Journalistic Ethics is implemented in Vanessa Anggel's Online Prostitution Reporting in East Java. Tribunnews.com. This research uses a descriptive content analysis method with a positive paradigm. This analysis is used to examine primary data in the form of news documents (in this study, East Java news, Tribunews.com). Of the 62 news stories featuring online prostitution cases involving Vanessa Angel in East Java, Tribunews.com. East Java, Tribunews.com does not fully implement Article 5 of the Journalistic Code of Ethics. So that East Java journalists indirectly, Tribunews.com also did not apply Article 2 of Law 40 of 1999 on the Press which obliged journalists to maintain professionalism in the process of presenting news.